Cahiers Ècole William Ponty ([Institut fondamental d'Afrique noire], 1989)
"Collection of papers written by students at the Ècole William Ponty in Senegal on the indigenous cultures of the Ivory Coast, ca. 1935-1946. Includes some papers by students from what was then Haute Côte d'Ivoire (Haute Volta, today Burkina Faso). Topics covered include agriculture, marriage, commerce, nutrition, games, and family" -- Cahiers Ecole William Ponty, index and reel guide, page 1.